GAMBARAN KEJADIAN HIPERTENSI PADA LANSIA DI DESA HITU KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH - Epi Dusra (Pusat riset dan Inovasi Nasional, 2022)
Hypertension is one of the most common cardiovascular diseases experienced by people with an increasing number of cases. and the purpose of this study was to describe the incidence of hypertension in the elderly in Hitu Village, Leihitu District, Central Maluku Regency. This study used a descriptive analytic research design, in which the researcher made direct observations on the respondents and distributed questionnaires using a descriptive approach to describe the incidence of hypertension in Hitu Village. The population in this study amounted to 23 respondents with the sampling technique that is total sampling and the samples found amounted to 23 respondents. Data analysis was carried out in the form of univariate analysis which was carried out using a computerized process and presented in the form of tables and narratives. The results of the study showed that many respondents were 60-65 years old, 34.8% In terms of gender, it was found that many respondents were women, totaling 17 respondents or with a percentage of 73.9%. In the last education respondents had the last education was SD as many as 18 respondents (78.3%). In the respondents who had a family history, that is, they did not have a family history of hypertension, as many as 13 respondents (56.5%). In terms of job characteristics, it can be seen that many respondents have jobs as IRT as many as 21 respondents (95.6%). It was concluded that the characteristics that best describe the incidence of hypertension in the elderly in this study were the respondent's gender, education and occupation.